Optimalisasi Pendidikan Agama Islam Melalui Program Gerakan Cinta Al-Qur’an (Studi Di SMP Unggulan Al-Amin Ngamprah) - Pipih Nurhayati; Arif Hidayatulloh; Husni Rofiq (ISLAMICA, 2022)
Al-Qur’an al-Karim is the book of Allah SWT. which is a guide for humans. Humans will not be able to use the Qur'an as a guide if they do not understand the content and meaning of the Qur'an. The first step to understanding the Qur'an is to study the Qur'an. However, in reality, today's students are still many who have not been able to read the Qur'an properly. Based on the results of the BAQI STAI test in 2018/2019, students who have not been able to read the Qur'an are still 77.55%. This condition is very concerning with many students who have not been able to read the Qur'an, let alone make the Qur'an a guide in their lives. One of the reasons is the lack of love for the Qur'an. Researchers conducted research in an educational institution, namely Al-Amin Superior Middle School, which focused on the al-Qur’an Love Movement Program to overcome this condition. This study aims to determine how the al-Qur’an Love Movement Program results can optimize Islamic religious education in schools. This study uses descriptive qualitative research methods. The data collection techniques used are interviews, observation, and documentation studies. This data is analyzed by reducing, presenting, triangulation, and concluding. The results of this study found that the Qur'an Love Movement Program The al-Qur’an Love Movement has a series of activities: murojaah al-Qur’an, tadarus Al-Qur’an, tahsin al-Qur’an, tahfidz al-Qur’an, tafhim Al-Qur’an, lectures, comprehensive session, and graduation tahfidz. Furthermore, in the operationalization of each activity, including planning, implementation, monitoring, and evaluation, it is considered good and quite good when viewed from Permendiknas Number 47 of 2007 concerning Standards for Management of Education by Non-formal Education Units. This al-Qur’an Love Movement program produces students who can read the Qur'an well, hafidz Qur'an 1-2 Juz, and students have good manners, are honest, and are accustomed to doing good in their daily lives as a practice of the Qur'an. Thus the al-Qur’an Love Movement program can optimize Islamic Religious Education in schools.